IMPLEMENTASI NILAI-NILAI PENDIDIKAN ISLAM DALAM MEMBENTUK BUDAYA SEKOLAH DI MTsN KOTA BATU - Abdul Mufidz; Muhammad Hanif; Muhammad Sulistiono (VICRATINA, 2021)
Islamic characterization and the application of the values of islamic enrolment in his life, the study of religious education must always be sought to convey the values of islamic education to the education of the learner, and to make the learner an islamic character. However, the value of islamic education can also be extended and transcends the culture of islamic schools so that learners can not only understand the value of islamic education in theory but also apply it to the application made in school culture and therefore in MTSN stone city, implementing many of the islamic school's culturally, with the aim of religious breeding of students. Research shows that: 1) among the many traditional applications of schools in MTSN stone city are the following: between mutual respect and mutual respect, subvaluing the classroom, growing crops, making the works on maddingProviding a cafeteria of honesty 2) there are islamic education values on The school culture applied to MTSN stone city is, of course, disciplined, honest, creative.